THE ON- AND OFF-STATE GENERATIONS IN THE CASE OF THE THICK ACCRETION DISK AND UNDEFINED PRECESSION PERIOD. 3-D NUMERICAL HYDRODYNAMICAL SIMULATIONS IN ACCRETION DISK IN MICROQUASAR CYG X-1 - Nazarenko, V. V. (Одеські астрономічні публікації, 2019)
In the present work we have com- puted the thick accretion disk (the accretion disk with radiation pressure) for the case of undefined precession over very long time (more than 14 precession periods). The calculations show that in this case the origin of the ON-states and OFF-states are strong irregular in time. The calculations also show that the jet’s launches are taking place very suddenly over 7 ÷ 20 minutes of the orbital time. The jet’s launches over OFF-states occurs discrete as it is observed in real microquasars.